Belonging in Preschool—An Existential and Political Concern for Children - Anette Cecilia Emilson; Eva Marianne Johansson (Education Sciences)
Preschool as a place of learning consists of various communities and belongings created in the intersection between children, teachers, and policy. The very essence of a good life in preschool is characterised by the sort of communities and the opportunities for belonging available to children. Being able to participate in various communities and to experience belonging is central to the wellbeing of every child in preschool. The aim of this study is to gain knowledge about processes of belonging in preschool peer communities. The following research questions guide the study: What categorisations, positionings, and identifications appear in the interactions between the children? What ethical and political value preferences are at stake? The study applies Nira Yuval-Davis’s theory about the politics of belonging and her analytical framework is used to interpret and understand data, including analytical concepts such as categorisation and social positioning, identifications, and ethical and political value systems. A case study has been used to explore processes of belonging in rich detail. Data consist of video observations of interactions between children in a Swedish Early Childhood Education (ECE) institution. Findings reveal how the children’s categorisations lead to various positions, identifications, and opportunities for belonging. We show how a grounded position is established, and how categorisations are used to justify exclusion. The study also illustrates various approaches used by the children to gain a sense of belonging in peer communities, here conceptualised as confrontation, adaptation, and defence. A conclusion is that children’s categorisations are deeply embedded in the social structures of preschool and that the work with belonging needs to be on every teacher’s agenda.